2007
DOI: 10.1577/t06-064.1
|View full text |Cite
|
Sign up to set email alerts
|

Upstream Swimming Performance of Adult White Sturgeon: Effects of Partial Baffles and a Ramp

Abstract: The upstream passage of sturgeon (family Acipenseridae) past barriers such as dams has become a concern of fisheries managers in California. Knowledge about the swimming abilities of adult sturgeon species, particularly with relationship to fish ladders, is limited. Wild adult white sturgeon Acipenser transmontanus (n = 25; total length, 135–198 cm) captured in the San Francisco Estuary and Yolo Bypass toe drain were swum in a variable‐speed aluminum flume (24.4 m long × 2.1 m wide × 1.4 m deep) to evaluate sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 17 publications
0
38
0
Order By: Relevance
“…Few comparative studies have been completed on passage success in technical structures, particularly for small-bodied fishes (Schwalme et al 1985;Katopodis et al 1991;Katopodis 1992;Webber et al 2007). The dual-vertical-slot fishway facilitated moderate passage success of Rio Grande silvery minnow at the relatively low 78 cm/s water velocity.…”
Section: Fishway Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Few comparative studies have been completed on passage success in technical structures, particularly for small-bodied fishes (Schwalme et al 1985;Katopodis et al 1991;Katopodis 1992;Webber et al 2007). The dual-vertical-slot fishway facilitated moderate passage success of Rio Grande silvery minnow at the relatively low 78 cm/s water velocity.…”
Section: Fishway Studiesmentioning
confidence: 99%
“…Moderate passage success at the lower velocity was probably due to the absence of large eddies and high-velocity turbulent flows that were present in higher velocity Denil and single-vertical-slot fishways (Bestgen et al 2003), and the dual-verticalslot fishway at the high velocity, where passage success was negligible. High turbulence has been demonstrated to reduce passage success even in relatively large-bodied white sturgeon Acipenser transmontanus (Webber et al 2007), so the negative effect of turbulence on small-bodied Rio Grande silvery minnow was not surprising.…”
Section: Fishway Studiesmentioning
confidence: 99%
“…It is worth noting that the methods to determine distance travelled likely result in underestimates as they represent the minimum distance between two locations, and thus COT estimates may be artificially inflated, although path selection and the subsequent distance travelled by individuals through basins remains unknown. Previous studies have identified that the presence of turning basins increases passage failure and delays passage (Bunt et al, 2000;Silva et al, 2015;White et al, 2011), including for this species (Thiem et al, 2011). Webber et al (2007 recommended the inclusion of lower-velocity areas between higher-velocity passage areas for white sturgeon.…”
Section: Discussionmentioning
confidence: 84%
“…In terms of a time optimisation strategy, the absence of turning basins would be beneficial as the addition of large low-velocity regions appears to delay passage, presumably because of the absence of high velocity cues (Marriner et al, 2014). Indeed, the low-velocity range (0.51-0.68 m s −1 ) recommended by Webber et al (2007) exceeded that determined to be the threshold (0.45 m s −1 ) attraction velocity to initiate upstream swimming in white sturgeon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation